Molar pregnancy with normal viable fetus presenting with severe pre-eclampsia: a case report - Atuk, Freddie Anak (J Med Case Rep, 2018)
BACKGROUND: While gestational trophoblastic disease is not rare, hydatidiform mole with a coexistent live fetus is a very rare condition occurring in 0.005 to 0.01% of all pregnancies. As a result of the rarity of this condition, diagnosis, management, and monitoring will remain challenging especially in places with limited resources and expertise. The case we report is an interesting rare case which presented with well-described complications; only a few similar cases have been described to date. CASE PRESENTATION: We report a case of a 21-year-old local Sarawakian woman with partial molar pregnancy who presented with severe pre-eclampsia in which the baby was morphologically normal, delivered prematurely, and there was a single large placenta showing molar changes. CONCLUSION: Even though the incidence of this condition is very rare, recognizing and diagnosing it is very important for patient care and it should be considered and looked for in patients presenting with pre-eclampsia.